EVALUASI PROGRAM MANAJEMEN PEMBELAJARAN PADA SEKOLAH ADIWIYATA KALIMANTAN TIMUR - Mahmud, Muhammad Eka; Suratman, Suratman (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2019)
This study aims to analyze the evaluation of learning management programs in the field of Islamic education, so that the quality of learning in adiwiyata schools is truly in accordance with the wishes of the community at large. This research uses a qualitative approach with case study. The research site is at Sekolah Menengah Umum Negeri 8 Samarinda dan Sekolah Menengah Umum Negeri 1 Tenggarong, East Kalimantan. The results showed that The results showed that Islamic education learning management is done through planning, implementation, evaluation by integrating the principles of adiwiyata schools in learning, by implementing the principal's policy strategy through continuous planning, implementation, mentoring and evaluation. The achievement of the evaluation results of the management of Islamic religious education learning in the context of integrated learning is very significant, with a value of 7.75 (good), development of learning tools 7.59 (good), monolithic learning 7.19 (good), and through extracurricular activities 6, 90 (good). The impact of management learning in Islamic education is; (a) the establishment of cooperation between schools and related parties in environmental management, (b) creative and innovative teaching staff, and (c) familiar with the attitude of environmental love and the use of used materials.